De menselijke figuur in de kunst 1910-1960. - Bafcop, Marc; Salzmann, Siegfried; Lebeer, Louis, 1895-1986; Cultureel Centrum A. Spinoy, Mechelen (Mechelen : Stad Mechelen, 1971)
Appel, Karel ; Archipenko, Alexander ; Arp, Hans ; Bacon, Francis ; Balthus ; Barlach, Ernst ; Beckmann, Max ; Belling, Rudolf ; Brancusi, Constantin ; Brusselmans, Jan ; Cantre, Jan-Frans ; Cantre, Jozef ; Chagall, Marc ; Ciry, Michel ; Corinth, Lovis ; Daeye, Hippoliet ; Dali y Domenech, Salvador ; De Chirico, Giorgio ; Delvaux, Paul ; Derain, André ; De Smet, Gustave ; De Troyer, Prosper ; Dix, Otto ; Epstein, Sir Jacob ; Ernst, Max ; Gargallo, Palo ; Giacometti, Alberto, ; Grard, Georges ; Gris, Juan ; Gromaire, Marcel ; Grosz, George ; Heckel, Erich ; Hofer, Karl ; Jespers, Oscar ; Kandinsky, Wassily ; Kirchner, Ernst-Ludwig ; Kisling, Moise ; Klee, Paul ; Klimt, Gustav ; Kokoschka, Oskar ; Kollwitz, Käthe ; Labisse, Felix ; Landuyt, Octave ; Laurens, Henri ; Lehmbruck, Wilhelm ; Leger, Fernand ; Lipchitz, Jacques ; Macke, August ; Magritte, René ; Maillol, Aristide ; Manzu, Giacomo ; Marini, Marino ; Masereel, Frans ; Matisse, Henri ; Minne, Joris ; Modigliani, Amedeo ; Müller, Otto ; Moore, Henry ; Munch, Edvard ; Nolde, Emil ; Orlowski, Hans Otto ; Pechstein, Max ; Permeke, Constant ; Picabia, Francis ; Picasso, Pablo ; Rouault, Georges ; Schmidt-Rottluff, Karl ; Segonzac, André ; Seitz, Gustav ; Servaes, Albert ; Severini, Gino ; Sluyters, Jan ; Soutine, Chaim ; Tytgat, Edgard ; Van den Berghe, Frits ; Van de Woestijne, Gustave ; Van Dijck, Albert ; Van dongen, Kees ; Van Straten, Henri ; Villon, Jacques ; Von Jawlensky, Alexej ; Wijnants, Ernest ; Wotruba, Fritz ; Wouters, Rik ; Zadkine, Ossip
De menselijke figuur in de kunst 1910-1960, Cultureel Centrum A. Spinoy, Mechelen, sept. 71 - nov. 71
boek